2015
DOI: 10.1152/ajpheart.00421.2015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrite infusion on skeletal muscle vascular control during exercise in rats with chronic heart failure

Abstract: Ϫ to NO may impact exercise-induced hyperemia, particularly in muscles with pathologically reduced O 2 delivery. We tested the hypothesis that NO 2 Ϫ infusion would increase exercising skeletal muscle blood flow (BF) and vascular conductance (VC) in CHF rats with a preferential effect in muscles composed primarily of type IIb ϩ IId/x fibers. CHF (coronary artery ligation) was induced in adult male Sprague-Dawley rats. After a Ͼ21-day recovery, mean arterial pressure (MAP; carotid artery catheter) and skeletal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 53 publications
3
23
1
Order By: Relevance
“…Collectively, our findings indicate that acute NO À 3 supplementation increases muscle BF and VC, but does not reduce local tissue VO 2 , during rhythmic handgrip exercise in healthy humans. This increase in muscle perfusion and O 2 delivery could help explain improvements in exercise tolerance by improving metabolic control (Bailey et al 2009;Glean et al 2015;Kenjale et al 2011;Larsen et al 2010;Vanhatalo et al 2011).…”
Section: Effects Of Br On Forearm Vo 2 During Normoxic and Hypoxic Exmentioning
confidence: 99%
See 1 more Smart Citation
“…Collectively, our findings indicate that acute NO À 3 supplementation increases muscle BF and VC, but does not reduce local tissue VO 2 , during rhythmic handgrip exercise in healthy humans. This increase in muscle perfusion and O 2 delivery could help explain improvements in exercise tolerance by improving metabolic control (Bailey et al 2009;Glean et al 2015;Kenjale et al 2011;Larsen et al 2010;Vanhatalo et al 2011).…”
Section: Effects Of Br On Forearm Vo 2 During Normoxic and Hypoxic Exmentioning
confidence: 99%
“…Physiological Reports published by Wiley Periodicals, Inc. on behalf of The Physiological Society and the American Physiological Society. peripheral artery disease, chronic obstructive pulmonary disease, diabetes, and patients with angina (Boden et al 2012;Glean et al 2015;Kerley et al 2015;Shepherd et al 2015a,b;Zamani et al 2015). Specific to limb blood flow and BR ingestion, Casey et al observed improvements in hypoxic exercise vasodilation in older adults, thus eliminating the age-associated impairment that occurred prior to BR ingestion (Casey et al 2015).…”
Section: Potential Implicationsmentioning
confidence: 99%
“…40-45 Inorganic nitrate and nitrite improve skeletal muscle microvascular conductance during exercise 46 and increase capillary O 2 tension facilitating O 2 diffusion into muscle cells. 47 Nitrite increases mitochondrial efficiency in skeletal muscle 48 and improves insulin sensitivity and glucose uptake.…”
Section: Pathophysiology Of Hfpefmentioning
confidence: 99%
“…12 Thus, circulating nitrate/nitrite may serve as an alternative pool for bioactive NO, which can sustain/enhance NO signaling when the traditional pathway for NO generation is less functional. 9, 13 Indeed, nitrate/nitrite supplementation has been shown to increase blood flow to exercising muscle in rats with 14, 15 and without 16, 17 heart failure. NO-induced vasodilation during exercise may facilitate the matching of perfusion to metabolic activity.…”
Section: Introductionmentioning
confidence: 99%